Improving fatigue life and toughness in electron beam welded Ti–6Al–4V achieved through beta heat treatment for microstructure uniformity - Seongji Seo; A Ra Jo; Hyun Wook Lee; Sun Kwang Hwang; Jeongho Han; Jiyong Park (Journal of Materials Research and Technology)
Electron beam welding (EBW) offers significant production efficiency advantages for Ti alloys in aerospace applications. However, the formation of martensitic α′ in the weld joint reduces toughness and fatigue properties, posing safety challenges. To address these issues, this study investigates the effects of annealing below the β transus temperature (mill annealing, MA) and above the β transus temperature (beta annealing, BA) on the microstructure and mechanical properties of EBWed Ti–6Al–4V (Ti64). EBW produced α′ in both the fusion zone (FZ) and heat-affected zone due to rapid heating and cooling. MA transformed α′ into an α+β basketweave structure, but did not eliminate microstructural gradients. Conversely, BA produced a homogenized microstructure across all regions, characterized by a transformed β phase with a coarse α+β basketweave structure dominantly oriented with prismatic plane. Both annealing processes reduced the amount of low-angle grain boundaries in the FZ compared to the EBWed condition. BA achieved superior mechanical improvements, including a 20 % increase in tensile toughness, a 56 % improvement in fatigue life, and a 100 % improvement in impact toughness. These enhancements are attributed to uniform strain distribution and enhanced fracture resistance facilitated by the basketweave structure. Therefore, this study suggests that BA is the optimal heat treatment for Ti64 weld joint, significantly improving fatigue cycle and impact toughness, and is recommened for aerospace structural applications.